2021
DOI: 10.26740/nld.v2n2.p70-78
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Blended Learning in Teaching English at Senior High School in Sidoarjo

Abstract: Blended learning is a learning strategy that combines face-to-face learning (both traditional in-class and virtually with video conferences) with online learning (e-learning). Blended learning is used as the best solution for dealing with restrictions on large-scale activities in Indonesia due to the spread of the coronavirus. SMAN 1 Porong applies blended learning to ensure the teaching and learning process continues, especially in learning English. On the other hand, teachers in this school face challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The second study was reported by Firdaus and Astutik [17] pertaining to the use of blended learning in teaching English at Sidoarjo Senior High School. This study employed a qualitative descriptive method.…”
Section: Introductionmentioning
confidence: 99%
“…The second study was reported by Firdaus and Astutik [17] pertaining to the use of blended learning in teaching English at Sidoarjo Senior High School. This study employed a qualitative descriptive method.…”
Section: Introductionmentioning
confidence: 99%